Central Vertigo Disorder as Evidence of Creutzfeldt-Jakob Disease: A Case Report. Issue 3 (14th March 2023) - Costa Villela Ferreira, Luiza; Braz Rodrigues da Silva, Camila; de Pinho, Lilia Gama; Lima, Fernanda Vidigal Vilela; Dias, Claudia Marques; Bahmad, Fayez
Abstract : Objective: To report a case of Creutzfeldt-Jakob disease (CJD) that presented atypical initial manifestations and highlight the importance of complementary investigation to avoid diagnosis delay. Patients: A 54-year-old female patient who presented with vertigo with positional nystagmus, nausea, and vomiting as initial CJD manifestations. Intervention: Neuro-otological and brain magnetic resonance images, which showed abnormal hyperintense cortical signal in both hemispheres. Main Outcome Measure: We reached a presumptive diagnosis of the prion disease after the first magnetic resonance imaging. Eventually, the patient presented with typical neurological findings and met the criteria for probable CJD. Results: Our case report presents a patient with sporadic CJD who experienced dizziness as an initial manifestation and met the diagnostic criteria for probable CJD a few weeks after symptoms onset. Conclusion: We believe that this case may serve to help otolaryngologists pay better attention to cases of dizziness associated with neurological signs and highlight the importance of complementary investigation using magnetic resonance imaging and neuro-otological tests to prevent delayed or incorrect diagnosis.